2022
DOI: 10.1111/birt.12685
|View full text |Cite
|
Sign up to set email alerts
|

Breech specialist midwives and clinics in the OptiBreech Trial feasibility study: An implementation process evaluation

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…Multiple research papers have demonstrated that some women wish to plan a VBB rather than an elective caesarean birth (CB), and despite current guidance, most are not able to access that care option. 1,2 Our goal is to enable women to make informed decisions by providing them with reasonable options, rather than 'standard care'. We agree with you: this is inadequate and unsafe.…”
Section: Dear Editormentioning
confidence: 99%
“…Multiple research papers have demonstrated that some women wish to plan a VBB rather than an elective caesarean birth (CB), and despite current guidance, most are not able to access that care option. 1,2 Our goal is to enable women to make informed decisions by providing them with reasonable options, rather than 'standard care'. We agree with you: this is inadequate and unsafe.…”
Section: Dear Editormentioning
confidence: 99%
“…Qualitative data provided insight into observed differences in recruitment at centres with clinics and/or specialist midwives. (43,48) In interviews and informal contacts, women reported numerous incidences of imbalanced counselling in favour of caesarean birth as the only reasonable option from obstetricians, except for those involved in the study. They reported some instances of imbalanced counselling in favour of VBB as a low-risk option from midwives, except for those involved in the study.…”
Section: Trial Feasibility Recruitmentmentioning
confidence: 99%
“…Women also reported increased con dence to plan a VBB when they had a reasonably good chance of an experienced attendant, which they felt the OptiBreech care pathway provided them. (43,48) Staff shortages during the COVID-19 pandemic in uenced recruitment gures. For example, Sites 100A and 100B were not able to receive self-referrals throughout their participation on this study, despite multiple requests from women who wanted to transfer their care to an OptiBreech site to participate in the research.…”
Section: Trial Feasibility Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations